Species Diversity, Distribution and Standing Biomass Of Sublittoral Seaweeds of the St. Martin’s Island, Bangladesh (Bangladesh Journal of Plant Taxonomy, 2022)
Substantial works carried out for over nearly fifty years contributed around 200 taxa under 84 genera along Bangladesh coast specially the St. Martin’s Island (SMI) when only intertidal and knee to waist deep seaweeds were collected. Sub-littoral seaweed diversity, their distribution and standing biomass along the coast of the SMI with the assistance of Bangladesh Navy using underwater gears, still photography and videography up to a depth of 15 m, were first studied during March and April 2013. It revealed a total of 40 seaweed taxa of which 16 were browns,12 reds and 12 greens including two new variety Caulerpa chemnitzia var. irregulare Aziz et Alfasane and C. sertularioides var. robusta Aziz et Alfasane. Total taxa were low compared to 1990’s and early 2000’s affected by human activities and that some smaller forms were washed away by current and waves during collections. Depth profile showed occurrence of a total of 31 (77%) taxa within 1 m and 34 (85%) in the next 1 m (within 2 m) have been considered as highly productive zone; 27 (67%) taxa in the next 1 m (3rd 1m) depth have been considered as the medium productive zone. The lower productivity in the 3rd m depth measured was due to low light (only 16% of surface light 1350 μEm-2s-1), high Secchi Depth and TDS, all indicating limited light intensity. The number of organisms at 10 m depth decreased to 17 (42%) taxa and at 15 m depth only 4 (10%) taxa were present. The 10 to 15 m depth studied have been considered as low productive zone for March and April environment. The 4 taxa at 15 m were represented by Peyssonnelia polymorpha, Caulerpa taxifolia, Halimeda discoidea and Dictyota atomaria and considered as highly adaptive seaweeds. Of these P. polymorpha in particular could grow on bare boulders of upper intertidal zone under direct sunlight during lowest tide. The average wet biomass in March and April was 55 g m-2 and 902 g m-2, respectively where browns had highest (291.00 g m-2) followed by greens (118.6 g m-2) and reds (45.10 g m-2). Highest average biomass was at location D (696 g m-2) followed by B (179.90 g m-2), A (175.70 g m-2) and C (74.20 g m-2). Total standing sublittoral wet biomass around the SMI was estimated to be 148.50 metric ton for each month based on collections from a total of 50 sites and contribute mostly by Caulerpa chemnitzia var. irregulare Aziz et Alfasane, C. sertularioides var, robusta Aziz et Alfasane, C. furgusonii, Caulerpa taxifolia and Asparagopsis taxiformis. Higher Shannon-Weiner Index of diversity (H') occurred in March at Zone C (3.152) followed by A (2.778), D (2.284), E (1.95) and a minimum at Zone B (1.53). In contrast, Shannon-Weiner Index of diversity (H') showed the higher values at Zone F (2.60) followed by C (1.87), B (1.47), D (1.21) and Zone A showed minimum value (